Determinants of Farm Revenue in Pakistan (The Pakistan Development Review, 2006)
Will small farm viability decline with the reduction of average farm size in Pakistan? This paper addresses the determinants of rural household and farm-related income. Using the 2001 PIDE Household Survey, the approach developed captures the potential interactions between farm returns and household, farm, and factor market characteristics (schooling, family size, land tenure and operational size, access to water, credit, and capital). Econometric results show: (a) returns to additional schooling and the revenue elasticity of operated acres increase with farm size; (b) medium and large farm renters would be willing to pay more than observed rents, implying an incentive to increase farm size at the prevailing rental values; (c) owneroperated farms, landowners who also leases in, and fixed rental tenants earn higher revenues than sharecropping tenants. The difference, however, between landowner/fix-renter income and sharecropper income varies with family and farm size, as well as water use. While these results favour farm size increase, the results also show that off-farm and non-farm income sources are relatively more important for small farmers, contributing to their viability. JEL classification: D13, Q12, Q15 Keywords: Pakistan, Land Markets, Rural Factor Markets, Revenue Function